A study on factors that contribute towards employee performance at Majlis Perbandaran Sungai Petani Kedah / Marfuzah Dahalan and Suraya Shafie - Dahalan, Marfuzah; Shafie, Suraya (2018)
This study aims to investigate the factors of motivation, training and management support that contribute towards employee performance in Majlis Perbandaran Sungai Petani, Kedah. This study also aims to identify the most influential factor that contribute towards employee performance. A total of 162 employees from five department in Majlis Perbandaran Sungai Petani, Kedah were chosen to answer the questionnaire given. Correlation was used to test the relationship between two variables and Multiple Regression was used to determine the factor between the three independent variables. The findings of the study indicate that motivation, training and management support contribute towards employee performance. The findings shows that training was the most influential factor that contribute towards employee performance. It was suggested that to enhance the training towards employee in order to improve the performance. This study could contribute to the knowledge of the organization related to employee performance.